Application of Projection Methods of Multivariate Data Analysis in Eddy Current Testing of Materials; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Polyakov V. V.; Egorov A. V.; Pirogov A. A.; Kolubaev Е. А. Evgeny Aleksandrovich (2015, 2015)
Title screen